Respuestas

  • Usuario de Brainly
2013-09-04T16:26:46+02:00
Solución:
(-5/3a^(-3) + b^(-1) - a)^2 = [{-5/3a^(-3) + b^(-1)} - a]^2
................................... = [{-5/3a^(-3) + b^(-1)}^2 - 2(-5/3a^(-3)+b^(-1))(a) + a^2]
................................... = (-5/3a^(-3))^2 + 2(-5/3a^(-3)*(b^(-1)) + (b^(-1))^2 + 10/3a^(-2) - 2ab^(-1) + a^2
................................ = (25/9) a^-6 - (10/3)a^-3*b^-1 + b^(-2) + (10/3)a^(-2) - 2ab^(-1) + a^(2)
.......= 25/(9a^6) - 10/(3a^3b) + 1/b^2 + 10/(3a^2) - 2a/(b) + a^2 =>Respuesta.

Espero haberte ayudado. Suerte